A highly sensitive in vivo footprinting technique for condition-dependent identification of cis elements - Gorsche, Rita (Oxford University Press, 2014)
Knowing which regions of a gene are targeted by transcription factors during induction or repression is essential for understanding the mechanisms responsible for regulation. Therefore, we re-designed the traditional in vivo footprinting method to obtain a highly sensitive technique, which allows identification of the cis elements involved in condition-dependent gene regulation. Data obtained through DMS methylation, HCl DNA cleavage and optimized ligation-mediated PCR using fluorescent labelling followed by capillary gel electrophoresis are analysed by ivFAST. In this work we have developed this command line-based program, which is designed to ensure automated and fast data processing and visualization. The new method facilitates a quantitative, high-throughput approach because it enables the comparison of any number of in vivo footprinting results from different conditions (e.g. inducing, repressing, de-repressing) to one another by employing an internal standard. For validation of the method the well-studied upstream regulatory region of the Trichoderma reesei xyn1 (endoxylanase 1) gene was used. Applying the new method we could identify the motives involved in condition-dependent regulation of the cbh2 (cellobiohydrolase 2) and xyn2 (endoxylanase 2) genes.